Goldstandard bei der Implantatwahl zur operativen Therapie der Spondylitis/Spondylodiszitis - Wiedenhöfer, Bernd; Hemmer, Stefan; Akbar, Michael; Lehner, Burkhard; Schmidmaier, Gerhard (Der Orthopäde, 2012)
The operative therapy management of vertebral osteomyelitis including debridement and stabilization is well established. Autologous bone is the preferred graft material but is limited due to availability, failure of consolidation in large defects and donor morbidity. Titanium mesh cages are alternatively equally well evaluated and other materials are also mentioned. Immobilization of affected segments is the fundamental requirement for healing of osteomyelitis. The operative therapy of choice is meticulous debridement and internal stabilization of the defect. Autologous bone seems to provide the best conditions to bridge and consolidate defects. Bone marrow aspirate, reaming irrigator aspiration (RIA) and bone marrow protein (BMP) in combination with cages have the same qualities considering bone healing but they are not yet sufficiently evaluated for management of vertebral osteomyelitis. Autologous bone graft remains the gold standard, nevertheless, its disadvantages point out the need for alternative grafts. Titanium is well proven to provide stability but bone substitutes are not sufficiently evaluated but seem to be promising.
Gesehen am 07.05.2018